2000
DOI: 10.1053/rapm.2000.6444
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of intrathecally administered tetracaine commences at the posterior roots near entry into the spinal cord

Abstract: Our results suggest that the initial target of intrathecal tetracaine neurotoxicity may be the posterior roots at their entry into the spinal cord, where the axons are devoid of myelin sheath and thus representing a sensitive area for neurotoxic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
18
1
1
Order By: Relevance
“…In our previous study using the same protocol, we reported the induction of histological lesions by bupivacaine, mepivacaine, and prilocaine (each at eight times), 11 lidocaine (3.7 times), 9 and tetracaine (four times) 10 higher than their clinical respective concentrations. In the present study, the concentration experiment indicated that procaine, levobupivacaine, and ropivacaine did not induce lesions even when used at ten times the clinical concentrations, suggesting that these three agents are less toxic than the drugs tested previously.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our previous study using the same protocol, we reported the induction of histological lesions by bupivacaine, mepivacaine, and prilocaine (each at eight times), 11 lidocaine (3.7 times), 9 and tetracaine (four times) 10 higher than their clinical respective concentrations. In the present study, the concentration experiment indicated that procaine, levobupivacaine, and ropivacaine did not induce lesions even when used at ten times the clinical concentrations, suggesting that these three agents are less toxic than the drugs tested previously.…”
Section: Discussionmentioning
confidence: 95%
“…bupivacaine for the central nervous and cardiovascular systems in animals 4,5 and humans. [6][7][8] In a series of studies, we determined the neurotoxicities of lidocaine, tetracaine, bupivacaine, mepivacaine, prilocaine, and procaine [9][10][11][12] in a rat spinal model. These studies showed that all these agents, with the exception of procaine, were neurotoxic, with lesions displaying common features irrespective of the anesthetic agent and affecting mainly axons of the dorsal root entry zone.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Em local próxi-mo à raiz posterior, imediatamente antes da sua entrada na substância branca medular, encontra-se uma zona desmielinizada, que contém neurônios desnudos. Estes neurônios são mais sensíveis à neurotoxicidade de drogas introduzidas no líquor 27 . Para concluir, pode-se dizer que grandes volumes de lidocaí-na a 2% determinaram alterações histológicas sobre o tecido nervoso da medula espinhal, mais intensas que aquelas determinadas pela ropivacaína a 1%.…”
Section: Resultsunclassified
“…In a site close to the posterior root, immediately before its insertion in the spinal cord white matter, there is a demyelinized region with nude neurons. These neurons are more sensitive to neurotoxicity of drugs introduced in the CSF 27 . In conclusion, large 2% lidocaine volumes determine more severe histological changes on spinal cord nervous tissue as compared to 1% ropivacaine.…”
mentioning
confidence: 99%